Faster alpha-expansion via dynamic programming and image partitioning - Fontinele, Jefferson; Mendonca, Marcelo; Ruiz, Marco; Papa, Joao [UNESP]; Oliveira, Luciano; IEEE (Ieee, 2020)
Image segmentation is the task of assigning a label to each image pixel. When the number of labels is greater than two (multi-label) the segmentation can be modelled as a multi-cut problem in graphs. In the general case, finding the minimum cut in a graph is an NP-hard problem, in which improving the results concerning time and quality is a major challenge. This paper addresses the multi-label problem applied in interactive image segmentation. The proposed approach makes use of dynamic programming to initialize an alpha-expansion, thus reducing its runtime, while keeping the Dice-score measure in an interactive segmentation task. Over BSDS data set, the proposed algorithm was approximately 51.2% faster than its standard counterpart, 36.2% faster than Fast Primal-Dual (FastPD) and 10.5 times faster than quadratic pseudo-boolean optimization (QBPO) optimizers, while preserving the same segmentation quality.
Keywords: alpha-expansion; dynamic programming; multi-label; image segmentation